Family-Wide Evaluation of Multiple C2 Domain and Transmembrane Region Protein in Gossypium hirsutum - Hu, Qianqian; Zeng, Mengting; Wang, Miao; Huang, Xiaoyu; Li, Jiayi; Feng, Changhui; Xuan, Lijie; Liu, Lu; Huang, Gengqing (Frontiers in Plant Science, 2021)
Multiple C2 domain and transmembrane region proteins (MCTPs) are a group of evolutionarily conserved proteins and show emerging roles in mediating protein trafficking and signaling transduction. Although several studies showed that MCTPs play important roles during plant growth and development, their biological functions in cotton remain largely unknown. Here, we identify and characterize 33 GhMCTP genes from upland cotton (Gossypium hirsutum) and reveal the diverse expression patterns of GhMCTPs in various tissues. We also find that GhMCTP7, GhMCTP12, and GhMCTP17 are highly expressed in the main stem apex, suggesting their possible roles in shoot development. Through analyzing different cotton species, we discover that plant height is closely related to the expression levels of GhMCTP7, GhMCTP12, and GhMCTP17. Furthermore, we knock down the expression of GhMCTP genes using virus-induced gene silencing (VIGS) system in cotton and find that GhMCTP7, GhMCTP12, and GhMCTP17 play an essential role in shoot meristem development. GhMCTPs interact with GhKNAT1 and GhKNAT2 and regulate meristem development through integrating multiple signal pathways. Taken together, our results demonstrate the functional redundancy of GhMCTPs in cotton shoot meristem development and provide a valuable resource to further study various functions of GhMCTPs in plant growth and development.